PROGRAMMING SPECIALIST'S PROFESSIONAL DEVELOPMENT AS LIFELONG SELF-DETERMINATION AND SELF-ORGANIZATION PROCESS - Katane, Irēna; Katans, Edgars (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Programming specialists are more and more demanded by modern information society.  The programming specialist’s professional development begins at school, when the young people choose their professions. The professional development is a lifelong process that does not end after obtaining of formal education and professional qualification. It is the self-determination process within which the important aspects are the programming specialist’s motivation, professional self-improvement, self-education, self-assessment of own professional proficiency and self-management of own career. The professional development is a multi-stage and multi-level cyclic process as a result of which the programming specialist can turn from a beginner into a highly level professional. At the same time it is nonlinear process, because the programming specialist’s professional development might have its rise and fall. The aim of studies is to substantiate theoretically the programming specialists’ professional development as lifelong self-determination and self-organization process within the context of career development, creating the methodological base for the further studies. The programming specialist’s career could be studied: 1) as a lifelong process (the career going horizontally); 2) as the development up to a high position in an IT company (a career going vertically); 3) as an independent developer’s career, when commencing business at his or her own company and/or within the framework of planned project (start up).   The programming specialist’s professionalism is an integral entirety of his/her many qualities, where competency is important in several spheres, not only in programming.